Laboratory Evaluation of Steel Pipe Filled with Concrete Exposed to Heat Considering the Adhesion between Concrete and Steel (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Due to the progress of composite structures and its use in columns, consideration should be given to the slip effect between the steel and concrete component as well as the appropriate solution for the shear and shear stress transfer between the two materials and the use of maximum bearing capacity of concrete and steel in these structures.In this study, by conducting a push-out experiment unilaterally on a CFST column with a circular cross section under heat of the furnace and cooled, to evaluate the natural bonding interaction and bond stress behavior; The slip in different samples is discussed. The parameters studied in this study are the number of shear and heat applied to the specimens before cooling. The diameter-to-thickness ratio for the circular cross-section geometry is assumed to be a constant value of 70 and a number of welded shear zeros of 0, 4 and 6, and the operating temperature of the furnace at 250, 500 and 750 °C, respectively. All specimens were 14 cm in diameter and 30 cm in height.The compressive strength of the fixed concrete and its value is 21 MPa and the steel sheet used is ST37. Bond stress and hardness indices were evaluated for each sample. The results of the study showed that the shear parameter is the cause of the macro changes in the boundary between the steel pipe and the concrete component, which results in significant changes and significant increase in the indices, resulting in a high shear residual shear strength.